Solvent-free phenolated lignin-based polyurethane elastomer as well as preparation method and application thereof
The phenolic lignin-based polyurethane elastomer is synthesized by a solvent-free one-step method, and a dynamic phenol-type carbamate bond and hydrogen bond crosslinking network is used to form a dynamic phenol-type carbamate bond and hydrogen bond crosslinking network, solving the contradiction between the mechanical properties and dynamic mechanical properties of the polyurethane elastomer in the prior art, and achieving a high-performance and environmentally friendly polyurethane elastomer preparation.
Patent Information
- Application Number
- CN202411431371.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-10-14
AI Technical Summary
It is difficult to prepare polyurethane elastomers with excellent mechanical properties and good dynamic mechanical properties under solvent-free conditions, and traditional methods rely on petroleum resources, high costs and complex processes.
The phenolic lignin-based polyurethane elastomer was synthesized by a solvent-free one-step method, and the high phenolic hydroxyl content of the phenolic lignin was used to form a dynamic phenol-type carbamate bond and hydrogen bond crosslinking network to improve the mechanical and dynamic mechanical properties of the material.
The prepared polyurethane elastomer exhibits high strength and high toughness, good heavy processing properties, photothermal self-healing, solvent resistance and aging resistance, solving the contradiction between the mechanical properties and dynamic mechanical properties of traditional materials.
Smart Images

Figure BDA0005083767340000061 
Figure BDA0005083767340000071 
Figure BDA0005083767340000091
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polyurethane elastomers, and specifically relates to a solvent-free phenolic lignin-based polyurethane elastomer and a preparation method and application thereof. Background Art
[0002] Polyurethane elastomers are widely used in smart wearables, flexible drives, automobile manufacturing, biomedicine and other fields due to their excellent mechanical properties. However, in practical applications, these materials are inevitably damaged and have a limited lifespan. If they are directly discarded, it will cause problems such as resource waste and environmental pollution. Therefore, the preparation of polyurethane elastomers with both excellent mechanical properties and dynamic mechanical properties has attracted widespread attention. The good mechanical properties of polyurethane elastomers usually rely on strong covalent crosslinks, which limit the dynamic mechanical properties of the material. At present, most studies balance the mechanical properties and dynamic mechanical properties of polyurethane by designing non-covalent crosslinks (such as hydrogen bonds, ionic bonds, and coordination bonds) and dynamic covalent crosslinks (disulfide bonds, DA bonds, and boron ester bonds, etc.), but these methods rely on petroleum resources, are costly, and have complex processes.
[0003] Lignin is a natural green aromatic polymer with abundant reserves, and its molecular structure is rich in active functional groups such as phenolic hydroxyl groups. If lignin rich in phenolic hydroxyl groups is used to replace part of petroleum-based polyols to synthesize polyurethane elastomers, it will not only reduce the consumption of petroleum resources, but also obtain lignin-based polyurethane elastomers rich in dynamic phenolic urethane bonds, which is expected to solve the contradiction between the mechanical properties and dynamic mechanical properties of polyurethane elastomers.
[0004] Patent application CN109485824A discloses a method for using base-catalyzed depolymerization enzymes to decompose lignin to obtain low molecular weight partially depolymerized lignin, and using the depolymerized lignin to prepare a lignin-based polyurethane elastomer. Although the elastomer has good heavy processing performance, its mechanical properties are poor and the toxic organic solvent dimethylacetamide is used.
[0005] Patent application CN117843904A discloses a method for synthesizing lignin-based polyurethane elastomer by a one-step solvent-free method using low molecular weight lignin obtained by ethanol extraction. Although this synthesis process is simple and does not use volatile or high-boiling point toxic organic solvents, the retention rate of its mechanical properties after one reprocessing is less than 50%, and the reprocessing performance is poor.
[0006] Patent application CN114933689A discloses a method for synthesizing a lignin-based polyurethane elastomer in a one-step process without solvent or catalyst. Although the elastomer has good reprocessing performance, its tensile strength is only 12.5 MPa, the mechanical properties are poor, and the lignin substitution amount is low.
[0007] At present, it is still a huge challenge to prepare polyurethane elastomers with both excellent mechanical properties and good dynamic mechanical properties under solvent-free conditions. Summary of the invention
[0008] In order to solve the shortcomings and deficiencies of the prior art, the primary purpose of the present invention is to provide a method for preparing a solvent-free phenolic lignin-based polyurethane elastomer.
[0009] Another object of the present invention is to provide a solvent-free phenolic lignin-based polyurethane elastomer prepared by the above preparation method.
[0010] The lignin-based polyurethane elastomer prepared by the present invention is synthesized by a solvent-free one-step method, and the synthesized elastomer is high in strength and toughness, and has good heavy processing, light and heat self-healing, solvent resistance and aging resistance. The present invention overcomes the problems that traditional lignin-based polyurethane elastomers cannot take into account both mechanical properties and dynamic mechanical properties, poor compatibility between lignin and polyols during the synthesis process, low reaction activity, low lignin substitution, and the need to use toxic solvents.
[0011] Another object of the present invention is to provide an application of the above-mentioned solvent-free phenolic lignin-based polyurethane elastomer.
[0012] The purpose of the present invention is achieved through the following technical solutions:
[0013] A method for preparing a solvent-free phenolic lignin-based polyurethane elastomer comprises the following steps:
[0014] (1) mixing lignin and a phenolizing agent at 110 to 140° C., adding concentrated sulfuric acid, reacting at 90 to 140° C. for 2 to 4 hours, and purifying the product after the reaction to obtain phenolized lignin;
[0015] (2) uniformly mixing the long-chain polyol and the phenolic lignin obtained in step (1) to obtain a mixed alcohol dispersion;
[0016] (3) After dehydrating the mixed alcohol dispersion in step (2), a catalyst and an isocyanate are added, reacted, cured, and hot-pressed to obtain a solvent-free phenolic lignin-based polyurethane elastomer.
[0017] Preferably, the lignin in step (1) is at least one of industrial lignin and industrial lignin extracted by ethanol; the industrial lignin is at least one of enzymatic lignin extracted by fermenting wood fiber to produce ethanol, alkali lignin, a by-product of alkali pulping, and organic solvent lignin extracted from wood fiber; more preferably, it is at least one of alkali lignin and alkali lignin extracted by ethanol.
[0018] Preferably, the phenolizing agent in step (1) is at least one of phenol, catechol, resorcinol, hydroquinone and pyrogallol; more preferably at least one of catechol and phenol.
[0019] Preferably, the mass concentration of the concentrated sulfuric acid in step (1) is 96-98%, and the amount of concentrated sulfuric acid used is 8-12% of the mass of the lignin; more preferably, it is 10%.
[0020] Preferably, the mass ratio of the phenolizing agent to lignin in step (1) is (1-3):1; more preferably 3:1.
[0021] Preferably, the reaction temperature in step (1) is 110° C. and the reaction time is 2 h.
[0022] Preferably, the method for purifying the product in step (1) is: adding the reaction product mixture into an acetone-water mixed solvent to dissolve the product, then precipitating the product with dilute sulfuric acid, filtering to obtain a filter cake, and drying the filter cake to obtain phenolic lignin.
[0023] More preferably, the volume concentration of acetone in the acetone-water mixed solvent is 60-90%.
[0024] More preferably, the pH value of the dilute sulfuric acid is 1-2.
[0025] Preferably, the long-chain polyol in step (2) is at least one of polyethylene glycol (molecular weight 1000-6000), polytetramethylene glycol (molecular weight 1000-2000), polycarbonate glycol (molecular weight 1000-4000) and polycaprolactone glycol (molecular weight 1000-6000); more preferably at least one of polyethylene glycol (molecular weight 1000-6000) and polytetramethylene glycol (molecular weight 1000-2000).
[0026] Preferably, the mass fraction of the phenolic lignin in step (2) in the mixed alcohol dispersion is 5-50%, and more preferably 30%.
[0027] Preferably, the mixing in step (2) refers to blending at 90-120°C for 1-3 hours; more preferably, blending at 120°C for 1 hour.
[0028] Preferably, the dehydration in step (3) refers to vacuum dehydration at 105-120° C. for 1-3 h; more preferably, vacuum dehydration at 105° C. for 1.5 h.
[0029] Preferably, the reaction temperature in step (3) is 60-90°C, and the reaction time is 0.5-4h; more preferably, the reaction temperature is 70°C, and the reaction time is 0.5-2h.
[0030] Preferably, the isocyanate in step (3) is at least one of diphenylmethane diisocyanate (MDI), hexamethylene diisocyanate (HDI), 4,4'-dicyclohexylmethane diisocyanate (HMDI), polymethylene polyphenylene isocyanate (PMDI) and hexamethylene diisocyanate trimer; more preferably polymethylene polyphenylene isocyanate.
[0031] Preferably, the molar ratio of the isocyanate groups of the isocyanate in step (3) to the total hydroxyl groups in the mixed alcohol dispersion is 0.8:1 to 1.4:1; more preferably 1.2:1 to 1.3:1 or 0.9:1; most preferably 1.2:1 and 0.9:1.
[0032] Preferably, the catalyst in step (3) is at least one of dibutyltin dilaurate, dibutyltin oxide, didodecylsulfide dibutyltin, bismuth isooctanoate and bismuth neodecanoate; the mass of the catalyst accounts for 0.2-0.8% of the total mass of the mixed alcohol dispersion and the isocyanate; more preferably 0.5%.
[0033] Preferably, the curing temperature in step (3) is 45-65°C and the curing time is 8-24 hours; more preferably, the curing temperature is 55°C and the curing time is 12 hours.
[0034] Preferably, the temperature of the hot pressing molding in step (3) is 160-170°C, the pressure is 10-12 MPa, and the time is 15-20 min; more preferably, the temperature of the hot pressing molding is 165-170°C, the pressure is 10 MPa, and the time is 20 min.
[0035] The invention provides a solvent-free phenolic lignin-based polyurethane elastomer prepared by the method.
[0036] Compared with the untreated industrial lignin raw material, the phenolic lignin prepared by the present invention has a lower molecular weight, a significantly improved hydroxyl content, especially a significantly improved phenolic hydroxyl content, and a higher reaction activity. The lignin-based polyurethane elastomer prepared by using the phenolic lignin has a higher chemical cross-linking network density and exhibits excellent mechanical properties. At the same time, thanks to the phenolic hydroxyl content of the phenolic lignin close to 100%, the polyurethane elastomer constructs a dual dynamic network consisting of a phenolic urethane bond network and a hydrogen bond cross-linking network. The dual dynamic network, especially the phenolic urethane bond network, gives the lignin-based polyurethane elastomer excellent heavy processing performance and photothermal self-healing performance.
[0037] Application of the above-mentioned solvent-free phenolic lignin-based polyurethane elastomer.
[0038] More preferably, the solvent-free phenolic lignin-based polyurethane elastomer is used in the fields of smart wearables, automobile manufacturing, biomedical material preparation and flexible driving.
[0039] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0040] 1. The phenolic hydroxyl content of the phenolic lignin prepared by the present invention is as high as 99.8%, which is unprecedented in existing lignins, and the preparation process is simple and convenient, and can be applied to various basic researches.
[0041] 2. The present invention utilizes phenolic lignin in a one-step method to synthesize a high-performance solvent-free phenolic lignin-based polyurethane elastomer, thereby avoiding the use of high-boiling point or volatile toxic organic solvents. The synthesis process is green and simple, and is easier to industrialize.
[0042] 3. The solvent-free phenolic lignin-based polyurethane elastomer prepared by the present invention is rich in dynamic phenolic hydroxyl-type urethane bonds. The phenolic urethane bonds are dissociated dynamic bonds, that is, they dissociate at high temperatures, which significantly improves the mobility of polymer chain segments and rapidly reconstructs the polymer network, thereby showing excellent heavy processing performance and photothermal self-healing performance. The contradiction between the mechanical properties and dynamic mechanical properties of polyurethane elastomers is resolved. DETAILED DESCRIPTION
[0043] The present invention is further described in detail below in conjunction with examples, but the embodiments of the present invention are not limited thereto.
[0044] If no specific conditions are specified in the examples of the present invention, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. All raw materials, reagents, etc., whose manufacturers are not specified, are conventional products that can be purchased commercially.
[0045] Tensile test conditions: The hot-pressed elastomer was cut into standard dumbbell-shaped specimens with a length of 50 mm, a width of 4 mm, and a thickness of 0.5 mm, and the tensile gauge length was selected as 20 mm. A CMT electronic universal testing machine was used, the test temperature was room temperature, and the tensile rate was 200 mm / min.
[0046] The preparation method of phenolized lignin CAL and PAL is as follows: 60g of alkali lignin raw material (AKL) and 180g of catechol or phenol are mixed at 110°C for 1h, 6g of concentrated sulfuric acid (mass concentration is 98%) is added, and after reacting for 2h, the product is dissolved in an acetone aqueous solution (acetone volume concentration is 90%) and then an excess of dilute sulfuric acid solution (pH is 1.5) is added. The filter cake is filtered to obtain a filter cake, which is dried in a vacuum oven at 55°C for 24h and ground to obtain phenolized lignin powder CAL or PAL.
[0047] The preparation method of ethanol-extracted lignin is as follows: 1000 g of alkali lignin raw material (AKL) is dissolved in 5 L of anhydrous ethanol, mechanically stirred at 25°C for 4 hours, filtered and separated, and the filtrate is taken. The filtrate is evaporated to obtain a concentrated solution, and the concentrated solution is evaporated and dried in a vacuum oven to obtain ethanol-extracted lignin powder AOH.
[0048] The preparation method of phenolized ethanol-extracted lignin PAOH is as follows: 60g of ethanol-extracted lignin (AOH) and 180g of phenol are mixed at 110°C for 1h, 6g of concentrated sulfuric acid (mass concentration is 98%) is added, and after reacting for 2h, the product is dissolved in an acetone aqueous solution (acetone volume concentration is 90%) and then an excess of dilute sulfuric acid solution (pH is 1.5) is added. The filter cake is filtered to obtain a filter cake, which is dried in a vacuum oven at 55°C for 24h, and the phenolized ethanol-extracted lignin powder PAOH is obtained after grinding.
[0049] GPC test conditions for lignin:
[0050] (1) Before testing, the lignin samples were dried in a vacuum oven at 55 °C for 24 h.
[0051] (2) The dried lignin was dissolved in chromatographically pure tetrahydrofuran (THF) to a concentration of about 2 mg / mL, and then the prepared solution was filtered through a 0.45 um organic phase filter membrane. The filtrate was injected into a gel permeation chromatograph with a mobile phase of chromatographically pure THF at a flow rate of 1.0 mL / min.
[0052] Table 1 GPC data of alkali lignin before and after phenolization
[0053]
[0054] The molecular weights of AKL, CAL, PAL, AOH and PAOH were measured. From Table 1, it can be found that the relative molecular weights and dispersity coefficients of lignin CAL and PAL after phenolization were significantly reduced, and depolymerization, catechol grafting and demethylation reactions occurred during the phenolization process.
[0055] NMR phosphorus spectrum test conditions of lignin:
[0056] (1) AKL, CAL, PAL, AOH, PAOH and consumables (small glass bottles, magnetic beads, NMR tubes, tweezers, pipette tips, etc.) were dried in a vacuum oven at 55°C for 10 h;
[0057] (2) Preparation of solvent A: deuterated pyridine and deuterated chloroform are prepared into a mixed solvent A in a volume ratio of 1.6:1;
[0058] (3) Preparation of internal standard solution (IS): Use a 4 mL glass vial to peel off the tares, weigh about 0.018 g of borneol (internal standard), and record the actual mass m1; after peeling off the tares, add about 0.005 g of chromium acetylacetonate (relaxation agent), and record the actual mass m2; after peeling off the tares of the vial with the cap, add 1 mL of solvent A, shake well, and weigh its mass to obtain m3;
[0059] (4) Preparation of lignin NMR solution: Peel the vial, weigh about 0.03 g of lignin to be tested, and record the actual mass m L ; After adding the small magnetic particle, peel off the lid, add 0.1mL of internal standard solution, and record its actual mass m IS ; Add 0.5mL solvent A and shake well, stir magnetically for 12h to fully dissolve it; finally add 0.15mL phosphating reagent and the test can be carried out.
[0060] Table 2 Alkali lignin before and after phenolization 31 P NMR data
[0061]
[0062] The hydroxyl content of lignin before and after phenolization was measured. It can be seen from Table 2 that the alcoholic hydroxyl of lignin CAL after catechol phenolation was significantly reduced, the phenolic hydroxyl content (99.8%) was significantly increased, and the total hydroxyl content was significantly higher than that of AKL. Whether it is alkali lignin raw material or ethanol extracted lignin, the alcoholic hydroxyl of lignin after phenol phenolation is significantly reduced and the phenolic hydroxyl is significantly increased, which will be beneficial to the preparation of lignin-based polyurethane elastomers rich in dynamic phenolic urethane bonds.
[0063] Example 1
[0064] (1) 60 g of alkali lignin raw material (AKL) and 180 g of catechol were mixed at 110° C. for 1 h, 6 g of concentrated sulfuric acid (mass concentration of 98%) was added, and after reacting for 2 h, the product was dissolved in an acetone aqueous solution (acetone volume concentration of 90%) and then an excess of dilute sulfuric acid solution (pH of 1.5) was added. The filter cake was filtered to obtain a filter cake, which was dried in a vacuum oven at 55° C. for 24 h and ground to obtain catechol phenolized lignin powder CAL.
[0065] (2) 14 parts by weight of polyethylene glycol 1000 and 6 parts by weight of the above-mentioned phenolic lignin were mixed and stirred at 120° C. for 1 hour to obtain a dispersion of lignin and long-chain polyol polyethylene glycol 1000 with a CAL mass ratio of 30%.
[0066] (3) 8 parts by mass of the above dispersion were vacuum dehydrated at 105°C for 1.5 hours, then cooled to 70°C, 0.059 parts by mass of dibutyltin dilaurate and 3.82 parts by mass of polymethylene polyphenylene isocyanate (the molar ratio of the isocyanate group of the isocyanate to the total hydroxyl group in the polyol and lignin was 1.4) were added, and the reaction was stirred for 30 minutes. The obtained product was placed in a vacuum oven and cured at 55°C for 12 hours. The sample was hot-pressed at 170°C and 10MPa for 20 minutes using a flat plate vulcanizer to obtain a solvent-free lignin-based polyurethane elastomer with excellent mechanical properties and dynamic mechanical properties. The tensile test showed that the elongation at break of the sample was 513.3%, the tensile strength was 34.4MPa, the Young's modulus was 66.1MPa, and the toughness was 83.2MJ / m 3 , the elastic recovery rate is 99.0%.
[0067] Example 2
[0068] Step (1) is the same as in Example 1.
[0069] Step (2) is the same as in Example 1.
[0070] Step (3) is as follows: 8 parts by mass of a dispersion of lignin and polyols with a mass ratio of 30% by mass of CAL are vacuum dehydrated at 105°C for 1.5 hours, then cooled to 70°C, 0.058 parts by mass of dibutyltin dilaurate and 3.55 parts by mass of polymethylene polyphenylene isocyanate (the molar ratio of the isocyanate group of the isocyanate to the total hydroxyl group in the polyol and lignin is 1.3) are added, and the reaction is stirred for 30 minutes. The resulting product is placed in a vacuum oven and cured at 55°C for 12 hours. The sample is hot-pressed at 170°C and 10MPa for 20 minutes using a flat plate vulcanizer to obtain a solvent-free lignin-based polyurethane elastomer with excellent mechanical properties and dynamic mechanical properties. The tensile test shows that the elongation at break of the sample is 614.9%, the tensile strength is 38.0MPa, the Young's modulus is 17.4MPa, and the toughness is 96.3MJ / m 3 , the elastic recovery rate is 99.6%.
[0071] Example 3
[0072] Step (1) is the same as in Example 1.
[0073] Step (2) is the same as in Example 1.
[0074] Step (3) is as follows: 8 parts by mass of a dispersion of lignin and polyols with a mass ratio of 30% by mass of CAL are vacuum dehydrated at 105°C for 1.5 hours, then cooled to 70°C, 0.056 parts by mass of dibutyltin dilaurate and 3.28 parts by mass of polymethylene polyphenylene isocyanate (the molar ratio of the isocyanate group of the isocyanate to the total hydroxyl group in the polyol and lignin is 1.2) are added, and the reaction is stirred for 30 minutes. The resulting product is placed in a vacuum oven and cured at 55°C for 12 hours. The sample is hot-pressed at 170°C and 10MPa for 20 minutes using a flat plate vulcanizer to obtain a solvent-free lignin-based polyurethane elastomer with excellent mechanical properties and dynamic mechanical properties. The tensile test shows that the elongation at break of the sample is 812.0%, the tensile strength is 41.0MPa, the Young's modulus is 16.2MPa, and the toughness is 140.9MJ / m 3 , the elastic recovery rate is 99.4%.
[0075] Step (4) is as follows: cut the sample after the tensile test into pieces, continue hot pressing, repeat the above steps twice to obtain a reprocessed sample, and test its mechanical properties.
[0076] Step (5) is as follows: Place the sample in a 100°C thermal oxygen aging oven and perform a mechanical property test after aging for 3 days.
[0077] Table 3 Mechanical properties parameters of polyurethane elastomer after multiple hot pressing in Example 3
[0078]
[0079] It can be seen from Table 3 that after two hot pressings, the tensile strength, elongation at break and toughness of the sample are still as high as 38.4MPa, 901.4% and 131.4MJ / m 3 , the tensile strength, elongation at break and toughness retention were 93.7%, 111.0% and 93.3%, respectively. The sample showed very excellent reprocessing performance, which was related to its abundant phenolic urethane bonds. However, after three hot pressings, the mechanical properties of the sample decreased significantly, which was caused by the aging of the PEG chain segments after multiple hot processing.
[0080] Table 4 Mechanical properties parameters of polyurethane elastomer of Example 3 after aging for three days
[0081]
[0082] It can be seen from Table 4 that the mechanical properties of the sample remain basically unchanged after three days of thermal oxidative aging. After three days of aging, the tensile strength and elongation at break of the sample are 40.9 MPa and 704.1%, respectively, and the retention rates are as high as 99.8% and 86.7%, respectively, showing excellent resistance to thermal oxidative aging. This is due to the rich phenolic hydroxyl groups in lignin.
[0083] Example 4
[0084] Step (1) is the same as in Example 1.
[0085] Step (2) is the same as in Example 1.
[0086] Step (3) is as follows: 8 parts by mass of a dispersion of lignin and polyols with a mass ratio of 30% by mass of CAL are vacuum dehydrated at 105°C for 1.5 hours, then cooled to 70°C, 0.055 parts by mass of dibutyltin dilaurate and 3.00 parts by mass of polymethylene polyphenylene isocyanate (the molar ratio of the isocyanate group of the isocyanate to the total hydroxyl group in the polyol and lignin is 1.1) are added, and the reaction is stirred for 30 minutes. The resulting product is placed in a vacuum oven and cured at 55°C for 12 hours. The sample is hot-pressed at 170°C and 10MPa for 20 minutes using a flat plate vulcanizer to obtain a solvent-free lignin-based polyurethane elastomer with excellent mechanical properties and dynamic mechanical properties. The tensile test shows that the elongation at break of the sample is 850.5%, the tensile strength is 34.6MPa, the Young's modulus is 8.5MPa, and the toughness is 111.3MJ / m 3 , the elastic recovery rate is 99.4%.
[0087] Example 5
[0088] Step (1) is the same as in Example 1.
[0089] Step (2) is as follows: 14 parts by weight of polytetramethylene ether diol 1000 and 6 parts by weight of phenolic lignin CAL in step (1) are mixed and stirred at 120° C. for 1 hour to obtain a dispersion of lignin and long-chain polyol polytetramethylene ether diol 1000 with a CAL mass ratio of 30%.
[0090] Step (3) is as follows: 8 parts by mass of a dispersion of lignin and polyols with a mass ratio of 30% by mass of CAL are vacuum dehydrated at 105°C for 1.5 hours, then cooled to 70°C, 0.056 parts by mass of dibutyltin dilaurate and 3.28 parts by mass of polymethylene polyphenylene isocyanate (the molar ratio of the isocyanate group of the isocyanate to the total hydroxyl group in the polyol and lignin is 1.2) are added, stirred and reacted for 2 hours, the resulting product is placed in a vacuum oven and cured at 55°C for 12 hours, and a flat plate vulcanizer is used to hot press the sample at 165°C and 10MPa for 20 minutes to obtain a solvent-free lignin-based polyurethane elastomer with excellent mechanical properties and dynamic mechanical properties. The tensile test shows that the elongation at break of the sample is 167.0%, the tensile strength is 27.5MPa, the Young's modulus is 117.4MPa, and the toughness is 30.2MJ / m 3 , the elastic recovery rate is 91.0%.
[0091] Example 6
[0092] Step (1) is the same as in Example 1.
[0093] Step (2) is the same as in Example 5.
[0094] Step (3) is as follows: 8 parts by mass of a dispersion of lignin and polyols with a mass ratio of 30% by mass of CAL are vacuum dehydrated at 105°C for 1.5 hours, then cooled to 70°C, 0.055 parts by mass of dibutyltin dilaurate and 3.00 parts by mass of polymethylene polyphenylene isocyanate (the molar ratio of the isocyanate group of the isocyanate to the total hydroxyl groups in the polyol and lignin is 1.1) are added, and the reaction is stirred for 2 hours. The resulting product is placed in a vacuum oven and cured at 55°C for 12 hours. The sample is hot-pressed at 165°C and 10MPa for 20 minutes using a flat plate vulcanizer to obtain a solvent-free lignin-based polyurethane elastomer with excellent mechanical properties and dynamic mechanical properties. The tensile test shows that the elongation at break of the sample is 293.0%, the tensile strength is 27.8MPa, the Young's modulus is 81.6MPa, and the toughness is 47.2MJ / m 3 , the elastic recovery rate is 89.8%.
[0095] Example 7
[0096] Step (1) is the same as in Example 1.
[0097] Step (2) is the same as in Example 5.
[0098] Step (3) is as follows: 8 parts by mass of a dispersion of lignin and polyols with a mass ratio of 30% by mass of CAL are vacuum dehydrated at 105°C for 1.5 hours and then cooled to 70°C, 0.054 parts by mass of dibutyltin dilaurate and 2.73 parts by mass of polymethylene polyphenylene isocyanate (the molar ratio of the isocyanate group of the isocyanate to the total hydroxyl group in the polyol and lignin is 1.0) are added, and the reaction is stirred for 2 hours. The resulting product is placed in a vacuum oven and cured at 55°C for 12 hours. The sample is hot-pressed at 165°C and 10MPa for 20 minutes using a flat plate vulcanizer to obtain a solvent-free lignin-based polyurethane elastomer with excellent mechanical properties and dynamic mechanical properties. The tensile test shows that the elongation at break of the sample is 390.3%, the tensile strength is 30.9MPa, the Young's modulus is 53.2MPa, and the toughness is 66.0MJ / m 3 , the elastic recovery rate is 89.8%.
[0099] Step (4) is as follows: cut the sample after the tensile test into pieces, continue hot pressing, repeat the above process four times to obtain a reprocessed sample, and test its mechanical properties.
[0100] Table 5 Mechanical properties parameters of polyurethane elastomer after multiple hot pressing in Example 7
[0101]
[0102]
[0103] It can be seen from Table 5 that after two hot pressings, the tensile strength, elongation at break and toughness of the sample are still as high as 35.3MPa, 504.7% and 91.3MJ / m 3 The tensile strength, elongation at break and toughness retention rates were 114.2%, 129.3% and 138.3% respectively, and the toughness retention rate of the sample after five hot pressings was still as high as 112.2%, showing very excellent heavy processing performance, which is related to its rich phenolic urethane bonds.
[0104] Example 8
[0105] Step (1) is the same as in Example 1.
[0106] Step (2) is the same as in Example 5.
[0107] Step (3) is as follows: 8 parts by mass of a dispersion of lignin and polyols with a mass ratio of 30% by mass of CAL are vacuum dehydrated at 105°C for 1.5 hours, then cooled to 70°C, 0.052 parts by mass of dibutyltin dilaurate and 2.46 parts by mass of polymethylene polyphenylene isocyanate (the molar ratio of the isocyanate group of the isocyanate to the total hydroxyl group in the polyol and lignin is 0.9) are added, and the reaction is stirred for 2 hours. The resulting product is placed in a vacuum oven and cured at 55°C for 12 hours. The sample is hot-pressed at 165°C and 10MPa for 20 minutes using a flat plate vulcanizer to obtain a solvent-free lignin-based polyurethane elastomer with excellent mechanical properties and dynamic mechanical properties. The tensile test shows that the elongation at break of the sample is 714.6%, the tensile strength is 44.6MPa, the Young's modulus is 26.0MPa, and the toughness is 148.0MJ / m 3 , the elastic recovery rate is 93.7%.
[0108] Step (4) is as follows: cut the sample after the tensile test into pieces, continue hot pressing, repeat the above process four times to obtain a reprocessed sample, and test its mechanical properties.
[0109] Step (5) is as follows: Place the sample in a 100°C thermal oxygen aging oven and perform a mechanical property test after aging for 3 days.
[0110] Step (6) is as follows: Cut the dumbbell-shaped spline in half and then use a power of 0.58 W / cm 2 The cross section was irradiated with near-infrared laser for 30 minutes to heal it, and the mechanical properties of the samples before and after photothermal self-healing were compared.
[0111] Table 6 Mechanical properties parameters of polyurethane elastomer after multiple hot pressing in Example 8
[0112]
[0113] It can be seen from Table 6 that after two hot pressings, the tensile strength, elongation at break and toughness of the sample are still as high as 43.7MPa, 700.5% and 139.7MJ / m 3 The tensile strength, elongation at break and toughness retention rates were 98.0%, 98.0% and 94.4% respectively, and the toughness retention rate of the sample after five hot pressings was still as high as 93.2%, showing very excellent heavy processing performance, which is related to its rich phenolic urethane bonds.
[0114] Table 7 Mechanical properties parameters of polyurethane elastomer of Example 8 after aging for three days
[0115]
[0116] It can be seen from Table 7 that the mechanical properties of the sample remain basically unchanged after three days of thermal oxidative aging. After three days of aging, the tensile strength and elongation at break of the sample are 40.7MPa and 730.5%, respectively, and the retention rates are as high as 91.3% and 102.2%, respectively, showing excellent resistance to thermal oxidative aging. This is due to the rich phenolic hydroxyl groups in lignin.
[0117] Table 8 Mechanical properties parameters of polyurethane elastomer after photothermal self-healing for 30 min in Example 8
[0118]
[0119] It can be seen from Table 8 that the power of the cut sample is 0.58W / cm 2 After 30 minutes of near-infrared laser irradiation, the tensile strength and elongation at break were 36.3 MPa and 631.6%, respectively, and the photothermal self-healing efficiency was as high as 81.4% and 88.4%, respectively, showing excellent photothermal self-healing performance. Therefore, the polyurethane elastomer prepared in Example 8 achieves a balance between mechanical properties and dynamic mechanical properties, and at the same time shows excellent resistance to thermal oxidative aging.
[0120] Example 9
[0121] Step (1) is the same as in Example 1.
[0122] Step (2) is the same as in Example 5.
[0123] Step (3) is as follows: 8 parts by mass of a dispersion of lignin and polyols with a mass ratio of 30% by mass of CAL are vacuum dehydrated at 105°C for 1.5 hours, then cooled to 70°C, 0.051 parts by mass of dibutyltin dilaurate and 2.18 parts by mass of polymethylene polyphenylene isocyanate (the molar ratio of the isocyanate group of the isocyanate to the total hydroxyl group in the polyol and lignin is 0.8) are added, stirred and reacted for 2 hours, and the resulting product is placed in a vacuum oven and cured at 55°C for 12 hours. The sample is hot-pressed at 165°C and 10MPa for 20 minutes using a flat plate vulcanizer to obtain a solvent-free lignin-based polyurethane elastomer with excellent mechanical properties and dynamic mechanical properties. The tensile test shows that the elongation at break of the sample is 713.8%, the tensile strength is 32.4MPa, the Young's modulus is 11.2MPa, and the toughness is 91.7MJ / m 3 , the elastic recovery rate is 94.4%.
[0124] Example 10
[0125] Step (1) is as follows: 60 g of alkali lignin raw material (AKL) and 180 g of phenol are mixed at 110° C. for 1 hour, 6 g of concentrated sulfuric acid (mass concentration is 98%) is added, and after reacting for 2 hours, the product is dissolved in an acetone aqueous solution (acetone volume concentration is 90%) and then an excess of dilute sulfuric acid solution (pH is 1.5) is added. The filter cake is filtered to obtain a filter cake, which is dried in a vacuum oven at 55° C. for 24 hours and ground to obtain phenol phenolated lignin powder PAL.
[0126] Step (2) is as follows: 14 parts by weight of polytetrahydrofuran ether diol 1000 and 6 parts by weight of phenolic lignin PAL in step (1) are mixed and stirred at 120° C. for 1 hour to obtain a dispersion of lignin and long-chain polyol polytetrahydrofuran ether diol 1000 in which the weight proportion of phenolic lignin PAL is 30%.
[0127] Step (3) is as follows: 8 parts by mass of a dispersion of lignin and polyols with a mass ratio of 30% by mass of PAL are vacuum dehydrated at 105°C for 1.5 hours, then cooled to 70°C, 0.051 parts by mass of dibutyltin dilaurate and 2.29 parts by mass of polymethylene polyphenylene isocyanate (the molar ratio of the isocyanate group of the isocyanate to the total hydroxyl group in the polyol and lignin is 0.9) are added, stirred and reacted for 2 hours, the resulting product is placed in a vacuum oven and cured at 55°C for 12 hours, and a flat plate vulcanizer is used to hot press the sample at 165°C and 10MPa for 20 minutes to obtain a solvent-free lignin-based polyurethane elastomer with excellent mechanical properties and dynamic mechanical properties. The tensile test shows that the elongation at break of the sample is 640.8%, the tensile strength is 37.1MPa, the Young's modulus is 13.1MPa, and the toughness is 90.7MJ / m 3 , the elastic recovery rate is 92.4%.
[0128] Step (4) is as follows: the sample after the tensile test is cut into pieces, hot pressed to obtain a reprocessed sample, and its mechanical properties are tested.
[0129] Table 9 Mechanical properties parameters of polyurethane elastomer after multiple hot pressing in Example 10
[0130]
[0131] It can be seen from Table 9 that the mechanical properties of the sample remain basically unchanged after two hot pressings, and the tensile strength, elongation at break and toughness are still as high as 35.6MPa, 719.4% and 101.1MJ / m 3 The tensile strength, elongation at break and toughness retention were 96.0%, 112.3% and 114.5%, respectively, showing excellent reprocessing performance, which is related to its abundant phenolic urethane bonds.
[0132] Embodiment 11
[0133] Step (1) is as follows: 60 g of ethanol-extracted lignin (AOH) and 180 g of phenol are mixed at 110° C. for 1 h, 6 g of concentrated sulfuric acid (mass concentration is 98%) is added, and after reacting for 2 h, the product is dissolved in an acetone aqueous solution (acetone volume concentration is 90%) and then an excess of dilute sulfuric acid solution (pH is 1.5) is added. The filter cake is filtered to obtain a filter cake, which is dried in a vacuum oven at 55° C. for 24 h and ground to obtain phenolized ethanol-extracted lignin powder PAOH.
[0134] Step (2) is as follows: 14 parts by weight of polytetrahydrofuran ether diol 1000 and 6 parts by weight of the phenolic ethanol extracted lignin PAOH in step (1) are mixed and stirred at 120° C. for 1 hour to obtain a dispersion of lignin and long-chain polyol polytetrahydrofuran ether diol 1000 in which the mass proportion of phenolic ethanol extracted lignin PAOH is 30%.
[0135] Step (3) is as follows: 8 parts by mass of a dispersion of lignin and polyols with a mass ratio of 30% by mass of PAOH are vacuum dehydrated at 105°C for 1.5 hours, then cooled to 70°C, 0.052 parts by mass of dibutyltin dilaurate and 2.43 parts by mass of polymethylene polyphenylene isocyanate (the molar ratio of the isocyanate group of the isocyanate to the total hydroxyl group in the polyol and lignin is 0.9) are added, stirred and reacted for 2 hours, and the resulting product is placed in a vacuum oven and cured at 55°C for 12 hours. The sample is hot-pressed at 165°C and 10MPa for 20 minutes using a flat plate vulcanizer to obtain a solvent-free lignin-based polyurethane elastomer with excellent mechanical properties and dynamic mechanical properties. The tensile test shows that the elongation at break of the sample is 762.2%, the tensile strength is 39.4MPa, the Young's modulus is 7.6MPa, and the toughness is 89.3MJ / m 3 , the elastic recovery rate is 95.4%.
[0136] Step (4) is the same as in Example 10.
[0137] Table 10 Mechanical properties parameters of polyurethane elastomer after multiple hot pressing in Example 11
[0138]
[0139] It can be seen from Table 10 that the mechanical properties of the sample remain basically unchanged after two hot pressings, and the tensile strength, elongation at break and toughness are still as high as 36.3MPa, 866.4% and 111.2MJ / m 3 The tensile strength, elongation at break and toughness retention were 92.1%, 113.7% and 124.5%, respectively, showing excellent reprocessing performance, which is related to its abundant phenolic urethane bonds.
[0140] Comparative Example 1
[0141] Step (1) is as follows: 14 parts by weight of polyethylene glycol 1000 and 6 parts by weight of alkali lignin raw material AKL are mixed and stirred at 120° C. for 1 hour to obtain a dispersion of lignin and long-chain polyol polyethylene glycol 1000 with a weight percentage of AKL of 30%.
[0142] Step (2) is as follows: 8 parts by mass of a dispersion of lignin and polyols with a mass ratio of AKL of 30% are vacuum dehydrated at 105°C for 1.5 hours, then cooled to 70°C, 0.054 parts by mass of dibutyltin dilaurate and 2.71 parts by mass of polymethylene polyphenylene isocyanate (the molar ratio of the isocyanate group of the isocyanate to the total hydroxyl group in the polyol and lignin is 1.2) are added, and the reaction is stirred for 30 minutes. The resulting product is placed in a vacuum oven and cured at 55°C for 12 hours. A flat plate vulcanizer is used to hot press the sample at 170°C and 10MPa for 20 minutes to obtain a solvent-free lignin-based polyurethane elastomer. The tensile test shows that the elongation at break of the sample is 512.7%, the tensile strength is 14.4MPa, the Young's modulus is 7.1MPa, and the toughness is 30.4MJ / m 3 , the elastic recovery rate is 99.0%.
[0143] Step (3) is as follows: the sample after the tensile test is cut into pieces, hot pressed to obtain a reprocessed sample, and its mechanical properties are tested.
[0144] Step (4) is as follows: Place the sample in a 100°C thermal oxygen aging oven and perform a mechanical property test after aging for 3 days.
[0145] Table 11 Mechanical properties parameters of polyurethane elastomers after multiple hot pressing of Comparative Example 1 and Example 3
[0146]
[0147] Table 11 shows the mechanical properties of polyurethane elastomers prepared by AKL (Comparative Example 1) and CAL (Example 3) after multiple hot pressing. It can be seen from the table that the mechanical properties of the elastomer prepared by CAL are significantly better than those prepared by AKL, because CAL has a low molecular weight, a high hydroxyl content, and a high crosslinking density of the obtained elastomer. The tensile strength, elongation at break and toughness of the elastomer prepared by Comparative Example 1 after two hot pressings are 6.98MPa, 376.1% and 10.7MJ / m 3 The tensile strength, elongation at break and toughness retention were 48.5%, 73.4% and 35.2% respectively, and the mechanical properties decreased significantly. Its reprocessing performance was significantly inferior to that of Example 3. The reason was that the elastomer prepared by AKL had fewer dynamic phenolic urethane bonds.
[0148] Table 12 Mechanical properties parameters of polyurethane elastomers of Comparative Example 1 and Example 3 after aging for three days
[0149]
[0150] It can be seen from Table 12 that the tensile strength and elongation at break of the elastomer prepared in Comparative Example 1 after three days of thermal oxidative aging are 18.7 MPa and 392.2%, respectively, and the retention rates are as high as 129.9% and 76.5%, respectively, showing excellent resistance to thermal oxidative aging. At the same time, the elastomer prepared in Example 3 also shows excellent resistance to thermal oxidative aging. The reason is that under the one-step solvent-free synthesis conditions, some phenolic hydroxyl groups in lignin, especially AKL, do not participate in the reaction. During the aging process, these unreacted phenolic hydroxyl groups not only slow down the erosion of the sample by hot oxygen, but also may undergo ester exchange reaction with the carbamate bond.
[0151] Comparative Example 2
[0152] Step (1) is as follows: 14 parts by weight of polytetramethylene glycol 1000 and 6 parts by weight of alkali lignin raw material AKL are mixed and stirred at 120° C. for 1 hour to obtain a dispersion of lignin and long-chain polyol polytetramethylene glycol 1000 with a weight percentage of AKL of 30%.
[0153] Step (2) is as follows: 8 parts by mass of a dispersion of lignin and polyols with a mass ratio of AKL of 30% are vacuum dehydrated at 105°C for 1.5 hours, then cooled to 70°C, 0.050 parts by mass of dibutyltin dilaurate and 2.04 parts by mass of polymethylene polyphenylene isocyanate (the molar ratio of the isocyanate group of the isocyanate to the total hydroxyl group in the polyol and lignin is 0.9) are added, stirred and reacted for 2 hours, and the resulting product is placed in a vacuum oven and cured at 55°C for 12 hours. A flat plate vulcanizer is used to hot press the sample at 165°C and 10MPa for 20 minutes to obtain a solvent-free lignin-based polyurethane elastomer. The tensile test shows that the elongation at break of the sample is 1064.8%, the tensile strength is 12.2MPa, the Young's modulus is 6.3MPa, and the toughness is 63.5MJ / m 3 , the elastic recovery rate is 97.7%.
[0154] Step (3) is the same as in Comparative Example 1.
[0155] Step (4) is the same as in Comparative Example 1.
[0156] Step (5) is as follows: Cut the dumbbell-shaped spline in half and then use a power of 0.58 W / cm 2 The cross section was irradiated with near-infrared laser for 30 minutes to heal it, and the mechanical properties of the samples before and after photothermal self-healing were compared.
[0157] Table 13 Mechanical properties parameters of polyurethane elastomers after multiple hot pressing of Comparative Example 2 and Example 8
[0158]
[0159]
[0160] Table 13 shows the mechanical properties of polyurethane elastomers prepared by AKL (Comparative Example 2) and CAL (Example 8) after multiple hot pressing. It can be seen from the table that the mechanical properties of the elastomer prepared by CAL are significantly better than those prepared by AKL, because CAL has a low molecular weight, a high hydroxyl content, and a high crosslinking density of the obtained elastomer. The tensile strength, elongation at break and toughness of the elastomer prepared by Comparative Example 2 after two hot pressings are 7.98MPa, 991.7% and 41.8MJ / m 3 The tensile strength, elongation at break and toughness retention were 65.4%, 93.1% and 65.8% respectively, and the mechanical properties decreased significantly. Its reprocessing performance was significantly worse than that of Example 8. The reason was that the elastomer prepared by AKL had fewer dynamic phenolic urethane bonds.
[0161] Table 14 Mechanical properties parameters of polyurethane elastomers of Comparative Example 2 and Example 8 after aging for three days
[0162]
[0163] As can be seen from Table 14, the tensile strength and elongation at break of the elastomer prepared in Comparative Example 2 after three days of thermal oxidative aging are 21.6 MPa and 866.0%, respectively, and the retention rates are as high as 177.0% and 81.3%, respectively, showing excellent resistance to thermal oxidative aging. At the same time, the elastomer prepared in Example 8 also exhibits excellent resistance to thermal oxidative aging. The reason is that under the one-step solvent-free synthesis conditions, some phenolic hydroxyl groups in lignin, especially AKL, do not participate in the reaction, and during the aging process, these unreacted phenolic hydroxyl groups, on the one hand, slow down the erosion of the sample by hot oxygen, and on the other hand, may undergo ester exchange reaction with carbamate bonds.
[0164] Table 15 Mechanical properties parameters of polyurethane elastomers after photothermal self-healing for 30 min in Comparative Example 2 and Example 8
[0165]
[0166] It can be seen from Table 15 that after the elastomer prepared in Comparative Example 2 was cut, it was then subjected to a 2 After 30 minutes of near-infrared laser irradiation, the tensile strength and elongation at break were 7.4 MPa and 990.6%, respectively, and the photothermal self-healing efficiency was 60.7% and 93.0%, respectively. Its photothermal self-healing performance was significantly worse than that of Example 8 because the elastomer prepared by AKL had fewer dynamic phenolic urethane bonds.
[0167] Comparative Example 3
[0168] Step (1) is as follows: 14 parts by weight of polytetramethylene glycol 1000 and 6 parts by weight of ethanol-extracted lignin AOH are mixed and stirred at 120° C. for 1 hour to obtain a dispersion of lignin and long-chain polyol polytetramethylene glycol 1000 with AOH accounting for 30% by weight.
[0169] Step (2) is as follows: 8 parts by mass of a dispersion of lignin and polyols with a mass ratio of 30% by mass of AOH are vacuum dehydrated at 105°C for 1.5 hours, then cooled to 70°C, 0.052 parts by mass of dibutyltin dilaurate and 2.46 parts by mass of polymethylene polyphenylene isocyanate (the molar ratio of the isocyanate group of the isocyanate to the total hydroxyl group in the polyol and lignin is 0.9) are added, and the reaction is stirred for 2 hours. The resulting product is placed in a vacuum oven and cured at 55°C for 12 hours. A flat plate vulcanizer is used to hot press the sample at 165°C and 10MPa for 20 minutes to obtain a solvent-free lignin-based polyurethane elastomer. The tensile test shows that the elongation at break of the sample is 777.7%, the tensile strength is 37.2MPa, the Young's modulus is 15.1MPa, and the toughness is 113.5MJ / m 3 , the elastic recovery rate is 96.1%.
[0170] Step (3) is the same as in Comparative Example 1.
[0171] Step (4) is as follows: Cut the dumbbell-shaped spline in half and then use a power of 0.58 W / cm 2 The cross section was irradiated with near-infrared laser for 30 minutes to heal it, and the mechanical properties of the samples before and after photothermal self-healing were compared.
[0172] Table 16 Mechanical properties parameters of polyurethane elastomers after multiple hot pressing of Comparative Example 3 and Example 8
[0173]
[0174] It can be seen from Table 16 that the tensile strength, elongation at break and toughness of the elastomer prepared in Comparative Example 3 after two hot pressings are 11.7 MPa, 439.4% and 27.5 MJ / m 3 , the tensile strength, elongation at break and toughness retention were 31.5%, 56.5% and 24.2% respectively, and the mechanical properties decreased significantly. Although the total hydroxyl content of AOH is the same as that of CAL, the reprocessing performance of Comparative Example 3 prepared by AOH is significantly worse than that of Example 8 prepared by CAL, because the phenolic hydroxyl content of AOH is significantly lower than that of CAL.
[0175] Table 17 Mechanical properties parameters of polyurethane elastomers after photothermal self-healing for 30 min in Comparative Example 3 and Example 8
[0176]
[0177] It can be seen from Table 17 that the elastomer prepared in Comparative Example 3 has a power of 0.58 W / cm after being cut. 2 After irradiation of the cross section with near-infrared laser for 30 minutes, the tensile strength and elongation at break were 16.2 MPa and 683.8%, respectively, and the photothermal self-healing efficiency was 43.5% and 87.9%, respectively. Its photothermal self-healing performance was significantly worse than that of Example 8. The reason is that the elastomer prepared with AOH has fewer dynamic phenolic urethane bonds.
[0178] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for preparing a solvent-free phenolic lignin-based polyurethane elastomer, characterized in that: The following steps are involved: (1) mixing lignin and a phenolizing agent at 110 to 140° C., adding concentrated sulfuric acid, reacting at 90 to 140° C. for 2 to 4 hours, and purifying the product after the reaction to obtain phenolized lignin; (2) uniformly mixing the long-chain polyol and the phenolic lignin obtained in step (1) to obtain a mixed alcohol dispersion; (3) After dehydrating the mixed alcohol dispersion in step (2), a catalyst and an isocyanate are added, reacted, cured, and hot-pressed to obtain a solvent-free phenolic lignin-based polyurethane elastomer.
2. The method for preparing a solvent-free phenolic lignin-based polyurethane elastomer according to claim 1, characterized in that: The mass ratio of the phenolizing agent to the lignin in step (1) is (1-3):1; The lignin in step (1) is at least one of industrial lignin and industrial lignin extracted by ethanol; the industrial lignin is at least one of enzymatic lignin extracted by fermenting wood fiber to produce ethanol, alkali lignin as a byproduct of alkali pulping, and organic solvent lignin extracted from wood fiber; The phenolizing agent in step (1) is at least one of phenol, catechol, resorcinol, hydroquinone and pyrogallol.
3. The method for preparing a solvent-free phenolic lignin-based polyurethane elastomer according to claim 1 or 2, characterized in that: The mass fraction of the phenolic lignin in the mixed alcohol dispersion in step (2) is 5% to 50%; The molar ratio of the isocyanate group of the isocyanate to the total hydroxyl group in the mixed alcohol dispersion in step (3) is 0.8:1 to 1.4:1; The long-chain polyol in step (2) is at least one of polyethylene glycol with a molecular weight of 1000 to 6000, polytetramethylene glycol with a molecular weight of 1000 to 2000, polycarbonate glycol with a molecular weight of 1000 to 4000, and polycaprolactone glycol with a molecular weight of 1000 to 6000; The isocyanate in step (3) is at least one of diphenylmethane diisocyanate, hexamethylene diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, polymethylene polyphenylene isocyanate and hexamethylene diisocyanate trimer.
4. The method for preparing a solvent-free phenolic lignin-based polyurethane elastomer according to claim 3, characterized in that: The reaction temperature in step (3) is 60-90° C. and the reaction time is 0.5-4 h; The curing temperature in step (3) is 45 to 65° C. and the curing time is 8 to 24 hours; The temperature of the hot pressing molding in step (3) is 160-170° C., the pressure is 10-12 MPa, and the time is 15-20 min.
5. The method for preparing a solvent-free phenolic lignin-based polyurethane elastomer according to claim 3, characterized in that: The mass concentration of the concentrated sulfuric acid in step (1) is 96-98%, and the amount of concentrated sulfuric acid used is 8-12% of the mass of the lignin; The catalyst in step (3) is at least one of dibutyltin dilaurate, dibutyltin oxide, di(dodecylsulfide)dibutyltin, bismuth isooctanoate and bismuth neodecanoate; the mass of the catalyst accounts for 0.2 to 0.8% of the total mass of the mixed alcohol dispersion and the isocyanate.
6. The method for preparing a solvent-free phenolic lignin-based polyurethane elastomer according to claim 3, characterized in that: The mass ratio of the phenolizing agent to lignin in step (1) is 3:1; The lignin in step (1) is at least one of alkali lignin and ethanol-extracted alkali lignin; The phenolizing agent in step (1) is at least one of catechol and phenol; The reaction temperature in step (1) is 110° C. and the reaction time is 2 h.
7. The method for preparing a solvent-free phenolic lignin-based polyurethane elastomer according to claim 3, characterized in that: The long-chain polyol in step (2) is at least one of polyethylene glycol with a molecular weight of 1000 to 6000 and polytetrahydrofuran ether diol with a molecular weight of 1000 to 2000; The mass fraction of the phenolic lignin in the mixed alcohol dispersion in step (2) is 30%; The reaction temperature in step (3) is 70° C. and the reaction time is 0.5 to 2 h; The molar ratio of the isocyanate group of the isocyanate to the total hydroxyl group in the mixed alcohol dispersion in step (3) is 1.2:1 to 1.3:1 or 0.9:1; The isocyanate in step (3) is polymethylene polyphenylene isocyanate.
8. The method for preparing a solvent-free phenolic lignin-based polyurethane elastomer according to claim 1, characterized in that: The method for purifying the product in step (1) is as follows: adding the reaction product mixture into a mixed solvent of acetone and water to dissolve the product, then using dilute sulfuric acid to precipitate the product, filtering to obtain a filter cake, and drying the filter cake to obtain phenolic lignin; The volume concentration of acetone in the acetone-water mixed solvent is 60-90%; The pH value of the dilute sulfuric acid is 1 to 2; The mixing in step (2) refers to blending at 90-120° C. for 1-3 hours; The dehydration in step (3) refers to vacuum dehydration at 105-120° C. for 1-3 hours.
9. A solvent-free phenolic lignin-based polyurethane elastomer prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the solvent-free phenolic lignin-based polyurethane elastomer according to claim 9.
Citation Information
Patent Citations
Thermosetting lignin-based polyurethane elastomer suitable for cyclic processing and preparation method thereof
CN109485824A
Intrinsic ultraviolet shielding polyurethane lignin composite film and preparation method thereof
CN113004557A
Modified lignin weather-resistant adhesive
CN113801616A
Solvent-free lignin-based polyurethane elastomer capable of being repeatedly processed and preparation method of solvent-free lignin-based polyurethane elastomer
CN113817130A
A reprocessable lignin-based polyurethane elastomer and its catalyst-free preparation method
CN114933689A